Climate Change, Sustainability and Disaster Management: The Imperative for Integrated Resilience - Shambhu B. Ukkali (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
This paper investigates the critical and rapidly intensifying nexus between anthropogenic climate change, the global pursuit of sustainable development, and the necessity for transformative Disaster Risk Reduction (DRR) and Disaster Management (DM) strategies. Climate change acts as a risk multiplier, dramatically increasing the frequency, intensity, and unpredictability of natural hazards, which consistently reverses developmental gains, particularly in vulnerable communities. The central argument is that the traditional, compartmentalized approach to disaster management-often reactive and hazard-specific-is fundamentally unsustainable in a warming world. Therefore, achieving long-term resilience requires the systemic integration of sustainability principles (social equity, economic viability, and environmental integrity) into proactive DRR and DM policy frameworks. The research analyzes global policy frameworks (Sendai Framework, Paris Agreement, SDGs) and employs case studies of Ecosystem-based Disaster Risk Reduction (Eco-DRR) to demonstrate the superior, cost-effective, and long-lasting protective benefits of a climate-informed, sustainable approach. The findings confirm that policy coherence and sustainable investment are not optional, but the new imperative for securing a viable future.